COMPARISON OF INVESTMENT STRATEGIES IN INNOVATION AND NON-INNOVATION PORTFOLIOS WITH PORTFOLIO OPTIMIZATION - Otniel William Hartanto; Sautma Ronni Basana (Finance and Investment Program, School of Business and Management - Petra Christian University, 2022)
This study aims to examine whether asset allocation strategies to the innovation sector can provide superior portfolio performance to investors. This type of research is comparative research using secondary data sources. The sample used is ETFs (Exchange Traded Funds) from investment companies namely BlackRock and Ark Invest since 2015. The focus of this study is to compare the performance of portfolios without an allocation to innovation assets and portfolios with allocations to innovation assets. This study analyzes the difference in performance between the two portfolios for various weightings and several portfolio optimization approaches, such as 'equal weighting' (1/N), optimality Lagrange, minimum-variance (MinVar), mean-variance (MV), and market-value weighted strategy.